Temporal selectivity of saflufenacil herbicide for the common bean crop of a brazilian oxisol (Acta Scientiarum. Agronomy, 2016)
The temporal selectivity of an herbicide refers to the time interval required between its soil application and crop sowing to prevent damage to crop development and reproduction. Using field bioassays, this study aimed to determine the temporal sensitivity of the herbicide saflufenacil when used with a crop. The study was conducted in two time periods during 2011/2012 and 2012/2013 and employed a split-plot, randomized block experimental design. The main plots were assigned to seven time intervals between herbicide application and bean sowing (0, 5, 10, 15, 25, 35, and 50 days), and the subplots were assigned to groups in which saflufenacil was absent or present (0 and 29.4 g ai ha-1). We determined the stand and the plant height at 7, 14, and 21 days after sowing (DAS), and the first pod height, the number of pods per plant, the number of seeds per pod and the grain yield at maturity. Saflufenacil negatively affected the development of the IPR-Tiziu bean; at 21 DAS, the stand and the plant height at maturity were the variables most sensitive to the herbicide. A minimum interval of 15 days between herbicide spraying and bean sowing was necessary to prevent a reduction in grain yield.